2022
DOI: 10.3389/fonc.2022.940056
|View full text |Cite
|
Sign up to set email alerts
|

Role of exosomal microRNAs in cancer therapy and drug resistance mechanisms: focus on hepatocellular carcinoma

Abstract: Extracellular vesicles (EVs), defined as intercellular messengers that carry their cargos between cells, are involved in several physiological and pathological processes. These small membranous vesicles are released by most cells and contain biological molecules, including nucleic acids, proteins and lipids, which can modulate signaling pathways of nearby or distant recipient cells. Exosomes, one the most characterized classes of EVs, include, among others, microRNAs (miRNAs), small non-coding RNAs able to reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 114 publications
0
6
0
Order By: Relevance
“…Dysregulation of miRNAs is frequently observed in drug‐resistant HCC or HCC cells 27 . miR‐224 is considered an oncogenic miRNA in liver cancer and data have related that the miR‐224 is related to the growth of HCC, and degradation of miR‐224 by autophagy inhibits HCC 28 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dysregulation of miRNAs is frequently observed in drug‐resistant HCC or HCC cells 27 . miR‐224 is considered an oncogenic miRNA in liver cancer and data have related that the miR‐224 is related to the growth of HCC, and degradation of miR‐224 by autophagy inhibits HCC 28 .…”
Section: Discussionmentioning
confidence: 99%
“…Combined application of Rop and Sor in clinical practice may potentially lower the dosage of Sor, reduce the occurrence of side effects and drug resistance in patients, and improve patient prognosis. These have significant clinical implications.Dysregulation of miRNAs is frequently observed in drugresistant HCC or HCC cells 27. miR-224 is considered an oncogenic miRNA in liver cancer and data have related that the miR-224 is related to the growth of HCC, and degradation of miR-224 by autophagy inhibits HCC 28.…”
mentioning
confidence: 99%
“…Exploring the probable processes that reduce therapeutic effectiveness would therefore aid in developing better cancer therapies. Exosomal miRNAs had a role in EGFR-TKI resistance as well [ 151 ]. For instance, Jing et al demonstrated the transfer of exosomal miR-21 from gefitinib-resistant H827R cells to gefitinib-sensitive HCC827 cells, where it subsequently stimulated AKT signaling and resulted in gefitinib resistance [ 152 ].…”
Section: Functional Implications Of Exosome Ncrna In Lung Cancermentioning
confidence: 99%
“…It constitutes approximately 75%–85% of all liver tumors ( Siegel et al, 2023 ). Despite advancements in hepatocellular carcinoma (HCC) treatment approaches, the therapeutic response of patients with intermediate to advanced HCC remains low due to factors such as tumor recurrence, metastasis, and drug resistance, resulting in a dismal prognosis ( Wang et al, 2022 ; Zelli et al, 2022 ). Since their discovery in 1983 ( Harding et al, 1983 ), extracellular vesicles (EVs) have evolved from being perceived as mere cellular waste disposal systems to a novel mechanism of intercellular communication.…”
Section: Introductionmentioning
confidence: 99%